Nickelocene SPM tip as a molecular spin sensor - Pinar Solé, Andrés; Kumar, Manish; Soler-Polo, Diego; Stetsovych, Oleksandr; Jelínek, Pavel (Journal of physics. Condensed matter, 2024)
Functionalization of a scanning microscopy probe with a single nickelocene allows reproducible spin-sensitive measurements of magnetic systems on surfaces. The triplet ground state of the nickelocene tip gives rise to a characteristic inelastic electron spin-flip excitation, which can change upon interaction with spin systems on the surface. These changes, together with theoretical simulations, enable us to determine the local spin moment on the surface. In this paper, we discuss the experimental and theoretical aspects of nickelocene-tip measurements. We rationalize the interactions between the nickelocene spin and the magnetic centers using a spin Heisenberg and dipole model, complemented by cotunneling theory, and compare the simulated dI/dV with selected experimental results. We developed a Python script to simulate this magnetic interaction, which is available on GitHub.
Keywords: spin Hamiltonian; STM; tip functionalization; cotunelling theory